Tian, J., Liu, L., Xiao, S.Y., Zhu, X.W., Wu, Y.J., Zhou, L., Yin, J., Peng, L., Cai, X.Z., Liu, L.H., Liu, Y.D., & Liu, K.M., (2018) Primulina hengshanensis (Gesneriaceae), a new species from Danxia landform in Hunan, China. Phytotaxa 333 (2): 293–297. - Tian, Jing; Liu, Lei; Xiao, Shun-Yong; Zhu, Xiao-Wen; Wu, Yao-Jing; Zhou, Liu; Yin, Juan; Peng, Ling; Cai, Xiu-Zhen; Liu, Lin-Han; Liu, Ying-Di; Liu, Ke-Ming (Phytotaxa, 2018)
N/A